A tensão entre a regra da maioria e a proteção de minorias na democracia brasileira contemporânea - Albuquerque, Hugo Thomas de Araujo (2016)
The problem addressed in the tension between majority rule and the protection of minorities in Brazilian Democracy Contemporary it is an very important issue for the brazilian Constitutional Law, even though the 1998 Brazilian Fundamental Law establishes a salutary rights system and warrants, including , protection of minorities, but, at the same time, it has a political order based on majority vote. This paradox reveals a cleavage within the constitutional system, which raises several questions: as a constitutional political system based on this principle can both realize the rights of minorities? Or, more accurately, what they are majorities and minorities? How can relate within a democratic regime? What would a democracy? What is the role of sovereign power? Raising such issues and raise possible ways of understanding is objective of this dissertation